(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article explores the continued popularity and robust capabilities of AutoCAD, the widely used drafting software. Highlighting its automated features and diverse language support, the text highlights the utility of the program for designers, engineers, scientists, and students in a variety of fields. Emphasizing the importance of mastering basic drawing and graphic commands, the text shows how AutoCAD enables users to create complex designs with precision and efficiency. It also addresses the role of computer graphics in teaching practical skills, including the creation of surfaces through the movement and intersection of lines. Overall, the text serves as an informative reflection on contemporary design practices and the importance of AutoCAD in education.